Jadwal A‘māl al-Aḥzāb al-Islāmīyah fī Indonesia al-Mu‘āṣirah: Bayn al-Sharī‘ah wa al-Dīmūqratīyah - Tasman, Tasman (Studia Islamika, 2013)
This article discusses the responses of the proponents of political Islam toward the downfall of New Order regime and in creating political power at grassroots level. This trend has been marked by the demand to include those ‘seven words’ of the Jakarta Chapter of 1945 into the constitution. This aspiration has been represented by three major Islamic parties: United Development Party (PPP); the Crescent Star Party (PBB); and the Justice Party (PK). However, this political Islam aspiration has also been expressed by Muslim–based parties, namely the Nation’s Awakening Party (PKB) and the National Mandate Party (PAN). These two parties represent Indonesia’s largest Muslim organisations, Nahdlatul Ulama (NU) and Muhammadiyah respectively. PKB and PAN do not have agendas to implement Islamic sharī‘ah. The two parties consider that, theoretically, a relation between Islam and politics exists but not in the formal sense of a governmental system.DOI: 10.15408/sdi.v20i1.351